PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK MENENTUKAN SUPPLIER IKAN TERI (Studi Kasus di PT. Urchindize Indonesia) - Noor Nailie Azzat; Mufidah Ulwiyatun Nafisah (Universitas Islam Nahdlatul Ulama Jepara, 2019)
Abstract PT Urchindize has more than 35 anchovy suppliers, although the company has many suppliers, it still often encounters obstacles. The obstacle felt by the company is that the supplier has not been able to meet a number of standard criteria owned by the company. The company has not yet implemented the proper selection and assessment method for suppliers. Based on this, the company must select suppliers to get suppliers who are truly able to meet company needs consistently and with quality. Based on the results of data processing using the Analytical Hierarchy Process (AHP) method, obtained the most influential criteria in supplier selection in the following order of priority: price criteria, delivery criteria, quality criteria, supplier relationship criteria, service criteria and responsibility. While the right supplier in the selection of suppliers for PT. Urchindize namely Mr. Ali Yudin became the main priority with a weight of 0.181, second was Mr. Akhsan with a weight of 0.159, third was Mr. Sugiyanto with a weight of 0.141, fourth was Mr. Junaidi with a weight of 0.118, the fifth was Mr. Masdawi with a weight of 0.102, the sixth was is Mrs. Mustarikah with a weight of 0.081, seventh is Mr. Sofyan and Mr. Idris with a weight of 0.073, eighth is Mr. Yusman with a weight of 0.044, the last priority is Mr. Abdul Rokhman with a weight of 0.037. Keywords: Supplier Selection, AHP